PENGARUH INSENTIF, LINGKUNGAN KERJA, DAN KOMUNIKASI TERHADAP KINERJA KARYAWAN CV PENTOL BAKSO OYE NGANJUK - Sulistiani, Finna (Prosiding Seminar Nasional Manajemen, Ekonomi dan Akuntansi, 2023)
Faced with competition in this era of globalization, companies are forced to work more efficiently to maximize business expansion and improve employee performance. The purpose of this study is to analyze (1) Incentives have a significant effect on employee performance at CV Pentol Bakso OYE Nganjuk. (2) work environment has a significant effect on employee performance CV Pentol Bakso OYE Nganjuk. (3) Communication has a significant effect on employee performance CV Pentol Bakso OYE Nganjuk. (4) Concurrent incentives, working environment and communication have a significant effect on the performance of CV Pentol Bakso OYE Nganjuk employees. The population of this study included CV Pentol Bakso OYE Nganjuk employees. Respondents for this study were 32 to use the total sampling method. And analyzed by multiple linear regression using SPSS Version 29 application.  The conclusion of this study is that (1) Partial incentives have a significant effect on the performance of CV Pentol Bakso OYE Nganjuk employees. (2) Working environment has a significant influence on employee performance CV Pentol Bakso OYE Nganjuk. (3) Partial communication has a significant effect on the performance of CV Pentol Bakso OYE Nganjuk employees. (4) Concurrent incentives, working environment and communication have a significant effect on the performance of CV Pentol Bakso OYE Nganjuk employees.